Hubungan Adversity Quotient dengan Kecenderungan Burnout pada Santri di Madrasah Aliyah Swasta Perguruan Islam Ar-Risalah Kota Padang - Dhelvina Rhesma; Murisal Murisal; Indah Andika Octavia (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Burnout is a condition of physical, emotional, and mental fatigue that can be experienced by students due to academic demands and crowded pesantren life. One of the factors that is suspected to play a role in reducing the tendency to burnout is the adversity quotient, which is the individual’s ability to face and overcome difficulties. This study aims to determine the relationship between adversity quotient and the tendency of burnout in students at Madrasah Aliyah Private Islamic College Ar-Risalah Padang City. This study uses a quantitative approach method with the person correlation technique. The total population in this study is 357 with a total of 177 samples. The sampling technique in this study is probability sampling and data collection using the Likert scale model. This study uses two scales, namely the adversity quotient from Paul G. Stoltz’s theory and the burnout scale based on Maslach’s theory. The results of this study show that students who have a moderate adversity quotient level with a total percentage of 68.9% and the level of student burnout tendency are also in the medium category with a total percentage of 76.3%. The results of hypothesis testing in this study showed that there was a negative relationship between adversity quotient and burnout in students, with r = -0.653 with a significance value of 0.000. This means that the higher the adversity quotient the lower the burnout, on the other hand, the lower the adversity quotient the higher the burnout.